BDS triple-frequency carrier phase combination smoothing pseudo-range algorithm. Issue 3 (March 2020) - Meng, Fanjun; Li, Shujun
Abstract: The carrier phase smoothing pseudo-range algorithm can effectively reduce the influence of multi-path effect and observation noise on pseudo-range positioning and improve the accuracy of pseudo-range positioning. Aiming at the problem that the existing classic Hatch filter smoother is susceptible to the cumulative interference of ionospheric delay in the pseudo-range smoothing process, the ionospheric delay and observed noise of the original double-difference observation are further weakened by constructing the optimal Beidou triple-frequency linear combination. The triple-frequency double-difference carrier phase combination are used to smooth the pseudo-range combination to replace the original observations. Finally, four groups of Beidou triple-frequency measured data with different baseline lengths, including 4m, 14.4km, 61.7km and 131.6km, are used to verify the algorithm. The theoretical derivation and effectiveness of the algorithm are verified by comparing and analyzing the smoothing effect of the algorithm in the following four groups of baseline conditions.